Antibacterial activity of Phyllanthus amarus extracts towards acute hepatopancreatic necrosis disease in white leg shrimps (Litopenaeus vannamei) caused by Vibrio parahaemolitycus and Vibrio sp. - Phương, Trần Vinh; Hân, Hoàng Thị Ngọc; Long, Đặng Thanh; Yến, Phạm Thị Hải; Linh, Nguyễn Quang (Hue University Journal of Science: Natural Science, 2019)
This paper presents the antibacterial activity of Phyllanthus amarus extracts towards hepatopancreatic necrosis in white leg shrimps (Litopenaeus vannamei) caused by Vibrio parahaemolitycus and Vibrio sp. in Thua Thien Hue, Vietnam. The results showed that the herbal extracts with a concentration of 250–1.000 mg/mL have an inhibitory diameter of 16.6–21.4 mm for V. parahaemolitycus and 17.6–23.6 mm for Vibrio sp. The minimum inhibitory concentration and minimum bactericidal concentration towards V. parahaemolyticus and Vibrio sp. are 125 and 500 mg/mL, and 62.5 and 250 mg/mL, respectively.